Nodavirus encephalopathy in turbot (Scophthalmus maximus): Inflammation, nitric oxide production and effect of anti-inflammatory compounds - Montes, Ariana; Figueras Huerta, Antonio; Novoa, Beatriz (Fish & Shellfish Immunology, 2010)
7 figuras, 2 tablas Nodaviruses are the etiological agents of one of the most serious viral diseases affecting marine fish aquaculture. Nodavirus infection produces an abnormal swimming behaviour and causes encephalopathy and retinopathy associated to important mortalities. The expression of TNF-α, IRF-1 and Mx was increased in turbot after nodavirus infection. A significant increase in the production of nitrogen radicals was also observed in experimentally infected turbot. Several anti-inflammatory compounds (the antioxidant N-acetylcysteine, cortisone, dexamethasone, prednisolone and aminoguanidine) were assayed to determine the role of inflammation on nodavirus infection. Cortisone and aminoguanidine were able to accelerate the mortality onset associated to nodavirus infection, modulating the gene expression of TNF-α and, in addition, modifying the arrival time of nodavirus to the brain. These results suggest the importance of early inflammatory processes to overcome the infection. This work was supported by the project CSD2007-00002 “Aquagenomics” funded by the program Consolider-Ingenio 2010 from the Spanish Ministerio de Ciencia e Innovación, project PGIDITOGRMA23501PR from Xunta de Galicia (and the Canadian-Spanish program NRC-MEC. Peer reviewed